2008
DOI: 10.1007/s00421-008-0887-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of secondary warm up following stretching

Abstract: Evidence suggests that static stretching inhibits muscular power. However, research does not reflect practice whereby individuals follow up stretching with secondary activity. This study investigated muscular power following stretching, and after a second bout of activity. Participants (n = 13) completed 3 randomized testing sessions which included a 5 min warm-up, followed by a vertical jump (VJ) on a force platform; an intervention (static stretching, dynamic, or control), followed by a second VJ. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 42 publications
5
52
1
4
Order By: Relevance
“…However, these claims are now refuted, with injury prevention regarded as unlikely (Shier 1999;Thacker et al 2004), while there is compelling evidence to show a decrease in strength (Bacurau et al 2009;Costa et al 2009;Herda et al 2008;Morse et al 2008), power (Manoel et al 2008;Samuel et al 2008), speed (Fletcher and Anness 2007;Fletcher and Jones 2004;Nelson et al 2005;Sayers et al 2008), jump performance (Holt and Lambourne 2008;Pearce et al 2009) and agility (Little and Williams 2006) linked to the incorporation of static stretches in a warm-up routine. In response to this evidence there has started to be a drift towards replacing the static stretch component of a warmup with dynamic stretching (deWned as controlled movement through the active range of motion for each joint, Fletcher and Jones 2004).…”
Section: Introductionmentioning
confidence: 95%
“…However, these claims are now refuted, with injury prevention regarded as unlikely (Shier 1999;Thacker et al 2004), while there is compelling evidence to show a decrease in strength (Bacurau et al 2009;Costa et al 2009;Herda et al 2008;Morse et al 2008), power (Manoel et al 2008;Samuel et al 2008), speed (Fletcher and Anness 2007;Fletcher and Jones 2004;Nelson et al 2005;Sayers et al 2008), jump performance (Holt and Lambourne 2008;Pearce et al 2009) and agility (Little and Williams 2006) linked to the incorporation of static stretches in a warm-up routine. In response to this evidence there has started to be a drift towards replacing the static stretch component of a warmup with dynamic stretching (deWned as controlled movement through the active range of motion for each joint, Fletcher and Jones 2004).…”
Section: Introductionmentioning
confidence: 95%
“…For example, vertical jumping ability has been shown to improve following strength-related WU (Burkett et al 2005;Gourgoulis et al 2003;Saez Saez de Villarreal et al 2007), but deteriorated if WU includes some stretching (Holt and Lambourne 2008;Young and Behm 2003). Moreover, the detrimental effect of stretching during WU has been reported to be reversed (Stewart et al 2007;Taylor et al 2008a, b) or not (Pearce et al 2009) if followed by a second bout of specific exercise. This might explain why it is so difficult to design the optimal (e.g., duration, intensity, recovery) WU routine that would be the perfect balance between benefits due to slight muscle temperature increase and neural adaptations without the detrimental effects of reduced muscle stiffness or contractility.…”
Section: Introductionmentioning
confidence: 96%
“…Although basketball coaches follow the aforementioned warm-up type, recent studies have examined the effect of static stretching during warm-up and found detrimental impact on performance (Faigenbaum et al 2006, Fletcher & Monte-Colombo 2010, Pearce et al 2009, Fowles et al 2000, Power et al 2004, Alikhajeh et al 2012, Little & Williams 2006, Chaouachi et al 2008, ο Nelson et al 2005, Sayers et al 2008, Fletcher & Jones 2004, Gelen 2010, Needman et al 2009, Winchester et al 2008Famisis 2015, Papadopoulos et al 2015. Reductions on vertical jump performance, lower limbs' power (Faigenbaum et al 2006, Fletcher & MonteColombo 2010, Pearce et al 2009), muscle strength (Fowles et al 2000;Power et al, 2004), power (Alikhajeh et al 2012, Little & Williams, 2006, acceleration (Chaouachi et al 2008, Nelson et al 2005, Sayers et al 2008)…”
Section: Introductionmentioning
confidence: 99%
“…Reductions on vertical jump performance, lower limbs' power (Faigenbaum et al 2006, Fletcher & MonteColombo 2010, Pearce et al 2009), muscle strength (Fowles et al 2000;Power et al, 2004), power (Alikhajeh et al 2012, Little & Williams, 2006, acceleration (Chaouachi et al 2008, Nelson et al 2005, Sayers et al 2008)…”
Section: Introductionmentioning
confidence: 99%